The Influence of Islamic Education in Africa - zaelani, Heri; Sukandar, Ahmad; Ahmad Fathurrahman, Asep (Zona Education Indonesia, 2023)
In 1990 and the Dakar Forum in 2000, several international partners (UNESCO, World Bank, UNICEF, United Nations Development Programme, etc.) decided to allocate considerable funds for the support and coordination of Quranic schools or madrassas. while hoping for greater coherence of this type of education with the national education plan. The reason for this interest in Islamic education lies in the role that these schools play in combating illiteracy and promoting the schooling of children. Indeed, in sub-Saharan Africa, as in other regions of the world, the generalization of primary education implies taking into account the teachings of Islam. This research applies a qualitative approach. Through this approach, researchers observe directly and invite informants to provide information about the object of research carried out with the aim of obtaining the best results. The subjects of this study were grade Islamic religious education in Africa. After data collection, the data is presented in the results of the study and then analyzed in the next discussion and will obtain conclusions as answers to problems in the implementation of religious culture in disciplining students. This research uses descriptive analytical methods, which are methods that function as an effort to obtain in-depth data. The data obtained from the resource persons are what facts make students motivated in participating in the organization of Afrika. Islamic education occupies a scattered and varied place depending on the country. The original cognitive system, a single pedagogy, certain cultural, religious and political functions make it a teaching with varied and evolving forms that make its analysis complex. The place of Islamic education in national education policy is still often marginal in sub-Saharan African countries